Implementation of media Mind Mapping and Power Points as A Media in Increasing Student Learning Motivation - Fajriyah, Lutfiana; Wardoyo, Cipto; Putri, Sheila Febriani (Asia Pacific Journal of Management and Education (APJME), 2020)
This study examines whether concept map and power point influence learning motivation. This study is a quantitative research using a quasy experiment method. The population used in this study is all students in SMKS Kepanjen 2017/2018. simple random sampling is used to obtain 32 students of class X AK 4 to apply mind mapping and 32 students of class X AK 1 to apply power point. Methods of data collection using a closed questionnaire using a Likert scale of 1 to 5. Descriptive statistics, independent sample t-test are employed to analyze the data. The results of this study show that (1) application of mind mapping further increases student’s motivation from the media power point with sig level of 0,003